(untitled) (Anclajes, 2022)
Most of the literature about Revista Moderna (1898-1903) and Revista Moderna de México (1903-1911) assumes that both publications integrate a single editorial project because of its affiliation with the Latin American modernism, particularly with that of the second generation, which presented a more decadent aspect. Although some scholars have noted the differences between the two formats, the petit revue and the North American styled magazine, the truth is that Revista Moderna de México has been reviewed in very similar terms to its predecessor, that is, as a literary, elitist and minority magazine, representative of a group with a specific literary positioning. In this paper, I will examine some of the devices that the editors of Revista Moderna de México used to articulate this transformation not only of format, but also of discursive positioning, mediated by the political and publishing market conditions from that time. This study pretends to draw attention to the set of negotiations and resistance that some agents of the literary field carried out through their professionalization process and their search for an alleged autonomy regarding other recognition figures during the transition from the 19th century to the 20th century.